STRUCTURE OF RECIPES TEXTS AND THEIR VARIETIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The thesis deals with representation in culinary names by analyzing the names of recipes in culinary magazines. The need for consideration in different linguistic units is due to its interdisciplinary and universal nature. The author analyzes the formal expression of the category of time in the semantic structure of culinary names.